Research of the clinical features, risk factors, and surgical diagnosis of intramural stones in patients with gallbladder stones - Xiaobing Luo; Hongying Cai; Xiaofeng Wang; Ruihong Ma; Gang Wang; Sangui Wang; Tie Qiao (Scientific Reports)
Abstract Crystals or stones within the gallbladder wall in patients with gallbladder stones (GBS) have been occasionally reported, but their clinical features and aetiology remain unclear. This retrospective study analysed 323 consecutive patients with GBS who underwent rigid choledochoscopic gallbladder-preserving cholecystolithotomy to determine the detection rate, clinical features, and potential risk factors of gallbladder intramural stones (IS). IS were found in 24.1% (78/323) of patients, characterised by distinct cholangioscopic findings, including stone shadows, yellow floating bands, or a combination of both within the gallbladder wall. Compared to patients without IS, those with IS had a higher prevalence of Clonorchis sinensis (C. sinensis) eggs (60.3% vs. 40.8%, P < 0.05) and elevated serum cholesterol, LDL cholesterol, and Apo-B levels (P < 0.05). However, stone composition and C. sinensis egg detection rates did not differ between intraluminal stones and IS within the same patient (P > 0.05). Logistic regression analysis revealed that IS were associated with C. sinensis infection and elevated Apo-B levels. In conclusion, IS share homology with intraluminal stones in the same patient with GBS and exhibit unique appearances in rigid choledochoscopy. For patients with GBS and IS, elevated serum Apo-B levels and C. sinensis infection were independent risk factors.